Phenotypic aging mediates the association between neutrophil percentage-to-albumin ratio and muscular dystrophies: a population-based study - Gong, Hongyang; Wang, Jiajun; Lin, Xiaomei; Huang, Shaoqun (Frontiers in Neurology, 2025)
BackgroundCurrent research on Muscular Dystrophies (MD) suggests that its occurrence is closely related to several mechanisms, including gene mutations, dystrophin deficiency, and alterations in the Akt/mTOR/p70S6K signaling pathway. The development of MD is influenced by factors such as genetics, inflammation, age, and underlying conditions. However, few studies have explored the association between the Neutrophil Percentage-to-Albumin Ratio (NPAR), phenotypic age, and MD. This study investigates the relationship between NPAR and MD and evaluates whether phenotypic age influences this association.MethodsSubgroup analysis, restricted cubic splines (RCS), and multivariable logistic regression were employed to explore the relationship between NPAR and MD. Additionally, mediation analysis was conducted to investigate the potential role of phenotypic age in the relationship between NPAR and MD.ResultsA total of 3,416 participants were included in this study, among whom 268 cases of MD were reported (6%, weighted). After adjusting for all variables using multivariable logistic regression, each unit increase in NPAR and phenotypic age was associated with a 29% (OR = 1.29, 95% CI: 1.19–1.39) and 7% (OR = 1.07, 95% CI: 1.03–1.12) increase in the odds of muscular dystrophies, respectively. Consistent results were obtained when NPAR and phenotypic age were categorized into tertiles, with a p for trend < 0.001. Restricted cubic spline (RCS) analysis indicated a linear positive correlation between NPAR and MD prevalence. Mediation analysis showed that 22.26% of the relationship between NPAR and MD was mediated by phenotypic age (p = 0.026).ConclusionThis study found a significant positive correlation between NPAR and MD, with phenotypic age acting as a partial mediator in this relationship. This finding underscores the potential of NPAR as a predictive marker for MD prevalence and highlights the importance of promoting healthy aging to reduce the risk of MD.